Admissibility analysis for linear singular systems with time-varying delays via neutral system approach. (March 2016) - Liu, Zhou-Yang; Lin, Chong; Chen, Bing
Abstract: This paper studies the admissibility problem for a class of linear singular systems with time-varying delays. In order to highlight the relations between the delay and the state, the singular system is transformed into a neutral form. Then, an appropriate type of Lyapunov–Krasovskii functionals is proposed to develop a delay-derivative-dependent admissibility condition in terms of linear matrix inequalities. The derivation combines the Wirtinger-based inequality and reciprocally convex combination method. The present criterion is also for the stability test of retarded and neutral systems with time-varying delays. Some examples are provided to illustrate the effectiveness and the benefits of the proposed method. Abstract : Highlights: The neutral system approach is extended to deal with singular systems with time-varying delays. A delay-derivative-dependent admissibility condition in terms of linear matrix inequalities is obtained. The proposed method can be used in testing stability of retarded and neutral systems with time-varying delays. Simulation examples are provided to illustrate the effectiveness and the benefits of the proposed method.